HPV immunisation: Moving toward a single dose?. (2nd August 2022) - Lepkowska, Dorothy
Abstract : New recommendations from the Joint Committee on Vaccination and Immunisation may lead to changes in the HPV immunisation schedule, Dorothy Lepkowska explains